Maximum Reciprocal Degree Resistance Distance Index of Unicyclic Graphs - Gai-Xiang Cai; Xing-Xing Li; Gui-Dong Yu (Discrete Dynamics in Nature and Society)
The reciprocal degree resistance distance index of a connected graph G is defined as RDRG=∑u,v⊆VGdGu+dGv/rGu,v, where rGu,v is the resistance distance between vertices u and v in G. Let Un denote the set of unicyclic graphs with n vertices. We study the graph with maximum reciprocal degree resistance distance index among all graphs in Un and characterize the corresponding extremal graph.